IDENTITAS MORAL DALAM CERPEN “BANJIR YANG DI KIRIM KE CHAMPOAN” (STUDI ANALISIS WACANA KRITIS) - Febria, Rhani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
modernization. The entry of foreign cultures also influences the mindset and policies that apply in society. The issue of moral identity is presented in the form of literary works, one of which is in the form of short stories. This study describes how the moral identity contained in short stories is seen from the linguistic level, discourse practice, and sociocultural practice. The researcher reviewed this research using the qualitative content analysis method of Norman Fairclough's critical discourse analysis. the approach which was used in this research is qualitative and Data collection techniques were done by downloading the short stories through online media. From the results of the research it can be concluded that 1. The study of moral identity can reveal power relations that the people's moral identity has been eroded by modernization, greedy rulers, and the powerlessness of the poor; 2. The dimensions of discourse practice show that the short stories presented are in accordance with Republika's vision and mission; 3. The dimensions of sociocultural (situational) practice are written according to the context of events when the text is published, namely the frequent occurrence of floods due to destruction of nature and lack of love for the environment. The implications of this research have the potential to contribute to literary understanding and literary research. By analyzing short stories with a critical discourse approach, researchers can provide insight into how literature reflects and shapes the moral identity of individuals and society.